XRF spectra belonging to report on quantification method based on XRF analysis. - Marei Hacke (Swedish National Heritage Board, 2023)
Accumulated spectra. Details in supporting information

S3 File. XRF instrument report quantitative analysis.

Report on quantification method based on XRF analysis.

https://doi.org/10.1371/journal.pone.0283539.s003

(DOCX)

Belonging to publication

Lagerqvist Alidoost A, Hacke M, Winther T, Sandström T (2023) A closer look at the Azzolino collection. PLOS ONE 18(4): e0283539. https://doi.org/10.1371/journal.pone.0283539
Keywords: metal impregnated paper; iron gall ink; XRF; History and Archaeology; Historia och arkeologi